Nilai-Nilai Pendidikan Multikultural dalam Buku Teks di Sekolah Dasar Kelas Atas - Afni Laila Nafi'ah; Hilmy Mahya Masyhuda (Institut Agama Islam Negeri Curup, 2021)
The value of multicultural education is very important to be taught to students not least at the elementary level unit education. This research will discuss the values of multicultural education in the texts in thematic textbooks at the elementary school level. This type of research uses library techniques with the object under study in the form of a textbook for elementary school students, and the class chosen in the textbook is class III-VI. In analyzing texts, researchers used qualitative research techniques and to obtain data researchers used reading and note-taking techniques. Besides the sampling technique or sampling is also taken by researchers so that the application is more directed at the data source in accordance with the problem. Content analysis techniques are also used to facilitate researchers in systematically organizing data collection. In the first data collection technique the researcher gave a signal to the data that wanted to be analyzed. Then the researcher categorizes the data according to the study, then an analysis is carried out by interpreting the categorized data. The results obtained in this analysis are Class III Integrated Thematic Textbooks VI has included multicultural education values such as educational values: tolerance, national spirit, love of the motherland or culture have been reflected in the texts presented in teaching materials. The quality of the content of multicultural education integrated in textbooks is adequate, although not all multicultural dimensions are well covered